Topography‐driven isolation, speciation and a global increase of endemism with elevation. Issue 9 (21st June 2016) - Steinbauer, Manuel J.; Field, Richard; Grytnes, John‐Arvid; Trigas, Panayiotis; Ah‐Peng, Claudine; Attorre, Fabio; Birks, H. John B.; Borges, Paulo A. V.; Cardoso, Pedro; Chou, Chang‐Hung; De Sanctis, Michele; de Sequeira, Miguel M.; et al.
Abstract: Aim: Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location: Thirty‐two insular and 18 continental elevational gradients from around the world. Methods: We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic ('percent endemism') in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results: Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions: Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.